2020
DOI: 10.1021/acs.molpharmaceut.0c00094
|View full text |Cite
|
Sign up to set email alerts
|

Cyclo-RGD Truncated Polymeric Nanoconstruct with Dendrimeric Templates for Targeted HDAC4 Gene Silencing in a Diabetic Nephropathy Mouse Model

Abstract: Diabetic nephropathy (DN), a chronic progressive kidney disease, is a significant complication of diabetes mellitus. Dysregulation of the histone deacetylases (HDACs) gene has been implicated in the pathogenesis of DN. Hence, the HDAC-inhibitors have emerged as a critical class of therapeutic agents in DN; however, the currently available HDAC4-inhibitors are mostly nonselective in nature as well as inhibit multiple HDACs. RNA interference of HDAC4 (HDAC4 siRNA) has shown immense promise, but the clinical tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 100 publications
(229 reference statements)
1
10
0
Order By: Relevance
“…HDAC4 contributes to podocyte injury and links renal injury to autophagy in DN, and in vivo gene silencing of HDAC4 reduces podocyte injury and proteinuria in diabetic rats ( Wang et al, 2014 ). Cyclo-RGD truncated polymeric nanoconstructs with dendrimeric templates for targeted HDAC4 gene silencing inhibited the progression of renal fibrosis in an STZ-induced DN model ( Raval et al, 2021 ). Silencing of HDAC9 attenuates glomerulosclerosis, inflammatory cytokine release, podocyte apoptosis and injury in db/db mice ( Liu et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…HDAC4 contributes to podocyte injury and links renal injury to autophagy in DN, and in vivo gene silencing of HDAC4 reduces podocyte injury and proteinuria in diabetic rats ( Wang et al, 2014 ). Cyclo-RGD truncated polymeric nanoconstructs with dendrimeric templates for targeted HDAC4 gene silencing inhibited the progression of renal fibrosis in an STZ-induced DN model ( Raval et al, 2021 ). Silencing of HDAC9 attenuates glomerulosclerosis, inflammatory cytokine release, podocyte apoptosis and injury in db/db mice ( Liu et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The MS/MS parameters for positive mode scan are 1000 V Nozzle voltage, 3000 V capillary voltage, 160 V fragmentor voltage, and 65 V skimmer. 17 2.5. Effect of Deprotected D2 Dendron Grafting on dCHA on RBCs, Hemolysis, Particle Size, and Zeta Potential.…”
Section: Methodsmentioning
confidence: 99%
“…For the evaluation of complex formation, a gel retardation assay was performed. 17 Control samples containing anti-miR21 (10,20,30,40, and 50 pmol) were also prepared. All the control samples were adjusted to the same volume (25 μL) as the sample with nuclease-free water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In cultured renal epithelial cells, MC1568 treatment and siRNA-mediated HDAC4 silencing also inhibited expression of several profibrotic markers, including α-SMA, fibronectin and collagen 1, as well as phosphorylation of Smad3 and NF-κB ( Xiong et al, 2019 ). Another study showed that HDAC4 silencing attenuated glomerular fibrosis and inhibited expression of the aformentioned fibrotic proteins in diabetic mice ( Raval et al, 2021 ). Thus, we suggest that among class IIa HDACs, HDAC4 may play a predominant role in promoting renal fibrosis.…”
Section: Introductionmentioning
confidence: 99%